PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA BENGKEL AHASS TRIO MOTOR PERINTIS BANJARMASIN - Masrifani -; Penta Lestarini Budiati; Nor Maulida (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2017)
Abstract,This research aimed to determine whether the quality of service which consist of tangible (X1), reliability (X2), responsiveness (X3), assurance (X4) and empathy (X5) influence simultaneously and partially on customer satisfaction (Y), as well as to determine the quality of service where the dominant influence on customer satisfaction in the Bengkel AHASS Trio Motor Perintis Banjarmasin.The population in this research are all customers in 2015 amounted to 34.092 customers. Samples were taken by 110 customers by accidental sampling. The analysis in this research using linear regression method.The result showed that the quality of service consisting of tangible (X1), reliability (X2), responsiveness (X3), assurance (X4) and empathy (X5) influence simultaneously on customer satisfaction. Responsiveness (X3), assurance (X4) and empathy (X5) partial effect on customer satisfaction, while tangible (X1) and reliability (X2) is not partial effect on customer satisfaction. Assurance (X4) variable is the dominant variable affecting customer satisfaction in the Bengkel AHASS Trio Motor Perintis Banjarmasin.